Government Intervention, Peers’ Giving and Corporate Philanthropy: Evidence from Chinese Private SMEs - Gao, Yongqiang (Journal of business ethics, 2015)
Institutional and resource dependence theories point at the roles of government and peers’ behavior as determinants of firms’ social behavior. This is tested in this research, with important implications for both theory and practice. Using data from a national survey of Chinese private small- and medium-sized enterprises (SMEs) in 2008, this paper examines the role of government intervention in corporate philanthropy (CP), as well as the moderation effect of peers’ giving (both industry and community peers’ giving). Results show that government intervention, when using a Marketization Index as a measure, increases CP (both giving probability and amount). In addition, the community peers’ giving enhances the positive effect of government intervention on SMEs’ giving. But the moderation effect of industry peers’ giving is generally not supported except when CP is measured as giving-to-sales. In general, community peers appear to be a clear reference for SMEs and, in relation to government intervention, exert a dominant isomorphic influence. The findings provide strong support to the neo-institutional theory perspective on philanthropy. Important theoretical and practical implications are suggested.